"Fishing" nano–bio interactions at the key biological barriers. Issue 12 (18th March 2021) - Rong, Jinyu; He, Yuan; Tang, Juanjuan; Qiao, Ruxia; Lin, Sijie
Abstract : Understanding nano–bio interactions is pivotal to the safe implementation of nanotechnology for both biological and environmental applications. Abstract : Understanding nano–bio interactions is pivotal to the safe implementation of nanotechnology for both biological and environmental applications. Zebrafish as a model organism provides unique opportunities to dissect nano–bio interactions occurring at different biological barriers. In this review, we focus on four key biological barriers, namely cell membrane, blood–brain barrier (BBB), skin and gill epithelia, and gastrointestinal tract (GIT), and highlight recent advancement achieved by using zebrafish to conduct both visualized observations and mechanistic investigations on a diversity of nano–bio interactions.